Ramadan Fasting in Health and Disease in 2021: A Narrative Review - Hassan-Beck, Reem; Hafidh, Khadija; Badi, Amal; Dougman, Khaled; Karmo, Mazn; Mir, Ruqqia; Beshyah, Salem A. (Ibnosina Journal of Medicine and Biomedical Sciences, 2022)
Introduction: The literature on the health aspects of Ramadan fasting (RF) is widely spread in many journals.Materials and Methods: This is a narrative review of data obtained from the PubMed database (National Library of Medicine, Bethesda, Maryland, United States). We used the search term “Ramadan fasting,” and relevant records were examined. The publications are narrated thematically.Results: The publications spanned fundamental, clinical, professional, cultural, and advocacy facets. The publications crossed conventional disciplinary lines and geographical locations and appeared in journals with different access systems. The contents are presented under the themes that emerged depending on the retrieved literature. This year basic coverage included changes in physiology and nutrition during Ramadan. However, the clinical issues included a wide range of topics. These included the impact of RF on nonalcoholic fatty liver disease and adjustments needed in endocrine replacement therapy for hypothyroidism and adrenal insufficiency. Coverage also included chronic kidney disease. The impact on maternal health, fetal well-being, and long-term effects of RF exposures were addressed in several studies. Studies in cardiovascular medicine focused on blood pressure and cardiovascular risk factors. Sports medicine and athletes' well-being received somewhat prominent coverage. The impact on renal function, particularly in patients with chronic kidney disease, was investigated by a few authors. Several groups addressed the eyes' structure and function, neurological conditions, especially headache disorders, and hematological and oncological conditions. Finally, the impact of RF on several aspects of mental health and well-being was addressed by various groups.Conclusions: Health aspects of RF received a sustained academic interest with a broad spectrum in 2021. This narration provides an overview of the year's scholarly health-related literature on various aspects of health and disease. It should help researchers and clinicians catch up quickly with the health concerns during Ramadan.
Keywords: cardiovascular; endocrine; literature; nutrition; physiology; pregnancy; professional; Ramadan; renal; research; sports medicine